Cost-effectiveness analysis of mepolizumab among patients with severe asthma from the Chinese societal perspective - Chaohao Shi; Yang Wang; Chongqing Tan; Xiaohui Zeng; Qiao Liu (PLoS ONE, 2026)
Background Patients with severe asthma, particularly those with an eosinophilic phenotype, face a limited array of treatment options. The Mepolizumab Efficacy in Patients with Severe Asthma (MENSA) trial (clinicaltrials.gov NCT03562195) has underscored the potential therapeutic benefits of mepolizumab as an adjunctive treatment for this patient group. However, the high cost of mepolizumab therapy presents significant economic challenges that may impede its widespread adoption in China. This study aims to assess the cost-effectiveness of mepolizumab from a societal perspective within the Chinese population suffering from severe asthma. Methods A Markov model spanning a lifetime horizon and employing a 2-week cycle was constructed. The model incorporated clinically significant exacerbations (CSEs) rates from the MENSA trial, along with asthma mortality rates, costs, and health state utilities, sourced from a broad spectrum of literature and national databases. Both costs and effectiveness outcomes were discounted annually at 5%. Incremental cost-effectiveness ratios (ICERs) were calculated as the primary model output and compared to a willingness-to-pay (WTP) threshold range of $15,217 to $38,042 per quality-adjusted life-years (QALY). The model’s robustness was evaluated through sensitivity analyses. Results The base-case analysis indicated an ICER of $848.79 per QALY for mepolizumab, fall below the lower limit of the predefined WTP threshold. Subgroup analyses confirmed this finding across different subpopulations. Deterministic sensitivity analyses showed that mepolizumab’s ICER remained below the lower limit of the predefined WTP threshold even under significant parameter variations. Probabilistic sensitivity analyses further demonstrated mepolizumab’s cost-effectiveness advantage over placebo. Conclusion Our study concluded that mepolizumab is a cost-effectiveness treatment option for severe asthma in China, applicable across various patient subgroups. This finding is crucial for healthcare decision-makers in China, where balancing cost and health outcomes is essential due to limited resources.